Hyperspectral Imaging (HSI) in anatomic left liver resection. (2019) - Sucher, Robert; Athanasios, Alvanos; Köhler, Hannes; Wagner, Tristan; Brunotte, Maximilian; Lederer, Andri; Gockel, Ines; Seehofer, Daniel
Highlights: Hyperspectral Imaging (HSI) is non-contact, non-ionizing and non-invasive. HSI detects tissue pathology based on spectral characteristics of different tissues. HSI is well suited for counter perfusion staining in anatomic liver resection. HSI can be used for future image guided liver surgery. Abstract: Introduction: Anatomic liver resection is based on the description of functional segments, which rely on the organs arterial and portal venous blood supply. Vascular inflow control of the left liver is performed by occlusion of the left hepatic artery (LHA) and left portal vein (LPV). Depending on the quality of the parenchyma a sharp demarcation line (Cantlie Line) between segments IV and V/VIII can hence be detected. Material and Methods: TIVITA® is a novel contact free tool which facilitates non-invasive hyperspectral imaging (HSI) and near infrared spectroscopy (NIRS) for the assessment of tissue- oxygenation (StO2 ) and perfusion (NIR Perfusion). We hypothesized that this imaging modality might be practicable to identify the future resection plane after left vascular inflow occlusion in anatomic liver resection. Presentation of Case: TIVITA ® is a viable tool for the identification of segments with reduced StO2 (inflow occlusion: 0.23 ± 0.03 vs normal: 0.50 ± 0.06) and NIR Perfusion (inflow occlusion: 0.02 ± 0.04 vs normal: 0.47 ± 0.06) and allows for a visual differentiation of well oxygenated, perfused (green) and low oxygenated, poorly perfused (blue) liver tissue in a patient undergoing left hemihepatectomy for hepatocellular carcinoma. Conclusion: Hyperspectral Imaging is an emerging optical technique with the potential to identify exact resection planes for anatomic liver resection based on the optically determined perfusion and oxygenation status of liver segments lined up for resection. This novel Hyperspectral Demarcation Technique (HSI DT) is non- contact, non-ionizing and non-invasive.